One-pot facile synthesis and electrochemical evaluation of selenium enriched cobalt selenide nanotube for supercapacitor application. Issue 11 (1st June 2021) - Subhadarshini, Suvani; Pavitra, Eluri; Rama Raju, Ganji Seeta; Chodankar, Nilesh R.; Mandal, Ajoy; Roy, Satyajit; Mandal, Suman; Rao, M.V. Basaveswara; Goswami, Dipak K.; Huh, Yun Suk; Das, Narayan C.
Abstract: The present study emulates a one-pot facile synthesis of selenium-enriched CoSe nanotube using a chemical bath deposition (CBD) procedure. Schematic incorporation of 3D Ni foam current collectors as substrates for the growth of CoSe–Se nanotubes helped us achieve a binder-less thin film coating. The controlled synthesis of CoSe–Se nanotube was carried out by optimizing the temperature and time of the deposition. CoSe–Se nanotubes were grown on a porous Ni foam substrate using lithium chloride as a shape directing agent. The study found that the one dimensional structure of the nanotubes with porous nature results in an uninterrupted network of electroactive sites. Due to the superior conductivity, the as-fabricated material exhibited excellent rate capability and a higher degree of electrolyte ion diffusion across the CoSe–Se crystal structure. The CoSe–Se@Ni foam electrodes exhibited a specific capacitance of 1750.81 F g −1 at 1 A g −1 . The electrode exhibited excellent cycling stability and showed a capacitance retention of 95% after 4000 charge-discharge cycles. Finally, an asymmetric supercapacitor (ASC) device was fabricated with the as-synthesized CoSe–Se@Ni foam electrode as the cathode, activated carbon@Ni foam electrode as the anode, and a thin filter paper separator soaked in 1 M aqueous KOH electrolyte solution. The ASC device showed a specific capacitance value of 106.73 F g −1 at 0.5 A g −1, and achieved an energy density of 37.94 Wh kg −1 at a power density of 475.30 W kg −1 . The ASC device was utilized in an extended potential window of 1.6 V. The fabricated device displayed exceptional cycling stability with a capacitance retention of 93% after 5000 charge-discharge cycles.